Macro and microplastics abundance on beaches of selected islands in Peninsular Malaysia / Nurul Nadia Aminuddin - Nurul Nadia , Aminuddin (2019)
The rapid development and heavy anthropogenic activities near the beach are believed to contribute to the abundance of plastic debris, which results in an array of negative effects to marine biota. This study discussed the macro and microplastics abundance on beaches of Malaysian islands namely, Pulau Besar, Langkawi Island, Sibu Island and Perhentian Island. The objectives of this study are to determine the current waste management and evaluate the cleanliness index (BCI) of the beach. It is also aimed to determine the composition of marine waste and abundance distributions of macro and microplastic as well as to determine their correlations. The BCI scores on each beach sites was evaluated by using a five point Likert scale ranged from 0 (very negative responses) to 4 (very positive responses). For the waste composition studies, debris on each beach sites were collected, weighed and counted after the segregation into 27 predetermined types. As for the microplastic quantification, a triplicate of 12.5 L of sediment samples was collected using 50 x 50 cm quadrat to a depth of approximately 5cm, at different tidal zones. The sediment samples were sieved to group them according to their respective sizes. Results indicated that, beach of Pulau Besar that faces the open sea was the cleanest with the highest BCI value (3). Recreational, fishing and shipping activities are the anthropogenic activities conducted on all the beaches studied. Marine waste found on these beaches includes hard plastic, film, polystyrene, paper, aluminium cans, and drinking packs. The distributions of macro and microplastic debris in this study are dependent of the economic activities of the respective beaches. The quantity of macroplastics was highest in Pinang Seribu Beach (103 items/m2), followed by beach of Sibu Island that faces the mainland (76 items/m2) and Tanjung Butong Beach (60 items/m2). The highest quantity of microplastics were collected at Pinang Seribu Beach with 2517 items/m2 and followed by beach of Sibu Island that faces the open sea with 401 items/m2. While fishing beaches have abundant quantities of plastic line, foam and film, recreational beaches accumulated more plastic film, fragment and foamed plastic. Remote beaches on Perhentian Island had the highest quantity of plastic foam, fragment and line. In general, a positive correlation (0.917) with R2 = 0.841 was found between the abundance of macro and microplastics on the selected beaches of Malaysian islands. This demonstrates that continued cleaning efforts are crucial to reduce the plastic debris pollution on beaches of Malaysian islands.